CHALLENGES AND STRATEGIES FOR VACCINATION AGAINST COVID-19 - Denilson Aurélio Soares, Cicero; Cristina Alves da Silva Lima, Hellen; Lívia Silva Fonseca Moreira de Medeiros, Renata; Silva Oliveira, Geane; Barros de Quental, Ocilma (Health and Society, 2022)
Introduction: The spread of COVID-19 occurred in an accelerated way and has become one of the great challenges of the 21st century, currently present on all continents. In view of this, the race for vaccination was fraught with several dilemmas and challenges for carrying out mass immunization, in this context, the present study aims to evaluate active search strategies for the advancement of vaccinated against Covid-19. Objective: To highlight the main difficulties faced in vaccination against covid-19, as well as the strategies used to achieve vaccination coverage. Methodology: This study was carried out through an integrative literature review, by searching for studies in scientific databases; LILACS, SCIELO and MEDLINE. Results and Discussions: A daily challenge debated in Primary Care is the population refusal to receive vaccine doses, as well as the population evasion to attend health units to take their second dose. In view of this, this health education process is yet another interface that acts as a resoluteness strategy in the process of acting against COVID-19. In this scenario, professionals performed different strategies in primary health care services, whose resolution is factual, such as active search and home vaccination, whose main objective was to achieve vaccination coverage and provide vaccination to all priority groups, as established. by MS. Conclusion: It can be seen that the challenges for equitable access to vaccination against COVID-19 are enormous, from producing adequate doses to organizing efficient vaccination programs and ensuring distribution that meets ethical and epidemiological standards.